Denosumab for the Treatment of Hypercalcemia in a Patient With Parathyroid Carcinoma: A Case Report - Roukain, Abdallah; Alwan, Heba; Bongiovanni, Massimo; Sykiotis, Gerasimos P.; Kopp, Peter A. (Frontiers in Endocrinology, 2022)
Refractory hypercalcemia is one of the major complications of parathyroid carcinoma. An 84-year old female patient presented with an acute confusional state due to hypercalcemia. This led to the diagnosis of primary hyperparathyroidism for which she underwent surgery. The initial histological diagnosis was interpreted as atypical parathyroid adenoma; the resection was microscopically incomplete. One year later, the patient presented with elevated calcium levels up to (3.89 mmol/l. Recurrent severe hypercalcemia required multiple hospitalizations. Review of the histology slides revealed that the initially resected lesion was in fact a parathyroid carcinoma. Treatment with the calcimimetic drug cinacalcet was poorly tolerated. Repeated administration of zoledronic acid only had transient effects on calcium levels, and bisphosphonate treatment was ultimately discontinued because of chronic renal failure. The patient then received denosumab (60 or 120 mg) when needed (nine doses over twenty months), the last dose in November 2020, which led to a reduction and control of here calcium levels. Currently, at three years after initial surgery, calcium levels are stable between 2.5-2.6 mmol/l and the patient has not required hospitalization for hypercalcemia for 10 months. In case of parathyroid carcinoma, en-bloc resection is the first treatment. Denosumab has proven its efficiency in treating hypercalcemia in malignancy. Several case reports studied denosumab in hypercalcemia due to parathyroid carcinoma, and the treatment were efficient to decrease levels of calcium when repeated as needed or monthly. We report another case of refractory hypercalcemia treated with several doses of denosumab in an patient with parathyroid carcinoma.